Associations of udder biometry with subclinical Mastitis in Gir crossbred cows - Shinde, A S; Mote, M G (Indian Journal of Dairy Science, 2021)
The investigation was undertaken on 110 Gir crossbred cows of different order of lactation and stage of lactation maintained at Research Cum Development Project on Cattle, MPKV, Rahuri. The overall least squares means of udder length, udder width, udder depth and udder circumference were 65.23 ± 1.45, 63.24 ± 1.45, 19.03 ± 0.51 and 86.49 ± 1.50 cm respectively. The least squares analysis of variance showed significant (P<0.05) effect due to order of lactation on udder length in crossbred cows. Also, order of lactation had significant (P<0.01) effect on udder width and udder circumference. However, stage of lactation exerted non-significant influence on all udder measurement traits. In crossbred cows udder length had positive and significant (P<0.01) correlation with udder width, udder circumference and udder depth. The correlation of udder width with udder circumference and udder depth was positive and highly significant (P<0.01). There was positive and significant (P<0.01) correlation of udder circumference with udder depth. The frequencies of trough, round, goaty and pendulous type udder in crossbred cows were 63.64%, 8.18%, 11.82% and 16.36% respectively. Among 110 cows 48 (43.64%) cows were found positive for subclinical mastitis. The higher occurrence of subclinical mastitis was observed in cows having pendulous udder (66.66%) followed by goaty (53.84 %), round (44.44 %) and trough (35.71 %) shape udder. Maximum number of positive subclinical mastitis cases were found in larger udder length (>75 cm), udder width (>75 cm), udder depth (>25 cm) and udder circumference (>95 cm). Highest occurrence (78.26%) of subclinical mastitis was found in cows of sixth and above lactation. Maximum occurrence of subclinical mastitis was noted in cows which were in late (46.15%) stage of lactation followed by early (40%) and mid (37%) stage of lactation. The traits udder shape, udder length and udder depth had positive and significant association with incidence of subclinical mastitis in crossbred cows.